The Ethics of Wasaṭīyah and the Pursuit of Gender Equality - Etin Anwar (International Institute of Islamic Thought, 2015)
The paper deals with the concept of wasaṭīyah (moderation) as an ethical framework for community making and its impact on the pursuit of gender equality. Qur’an 2:143 speaks about the correlation between making a fair community (al-ummah al-wasaṭ) and piety, which is inclusive of both men and women. As both terms are intertwined, any efforts to discuss wasaṭīyah must include how Muslims relate to God and how this relationship is exercised in all areas of their lives. Given that this intersection is a matter of ethics, my paper will demonstrate that wasaṭīyah affords the inclusion of both genders as ethical agents in the pursuit of a fair community. I first discuss how the ethics of wasaṭīyah provide a framework for community building by drawing some parallels between Prophet Muhammad’s creation of a fair and inclusive community and how Muslims could embody God’s message within themselves and their communities. I then show how including women in the community-making process echoes both the Islamic ethics of moderation and the value of women as ethical agents.